(untitled) (BIMRAD Journal, 2025)
Knowledge of strategic culture as a way of life provides the ways and means for a nation to design its national security architecture. It is significant for Bangladesh, a predominantly Muslim country encircled by India—a constitutionally secular republic that adorns Hindutva as its way of life. The constitution of Bangladesh, before the last amendment, pledged that the high ideals of absolute trust and faith in the Almighty Allah shall be the fundamental principles. This demands that the strategic culture of Bangladesh ought to point toward Islam as Bangladesh’s way of life. The research endeavors to evaluate the reality by identifying culture and its derivatives, followed by analyzing the history—the pointer of the country’s strategic culture. Cases of two of the greatest democracies, i.e., India and the USA, are briefly examined in light of their strategic cultures. The indivisible connections between absolute trust in the Almighty and the strategic culture of the people of Bangladesh are examined to articulate Bangladesh’s prosperity duo. BIMRAD Journal VOLUME 5, ISSUE 1, DEC 2024; PP-20-39